2020
DOI: 10.1177/0300891620919161
|View full text |Cite
|
Sign up to set email alerts
|

Primary leiomyosarcoma of the uterine cervix: report of 4 cases, systematic review, and meta-analysis

Abstract: Background: Primary cervical leiomyosarcomas (CLMS) constitute 21% of all cervical sarcomas. Because of their rarity, to our knowledge, fewer than 40 cases have been reported. The aim of this study is to evaluate the clinical and surgical–pathological features, prognosis, treatment options, and survival of primary CLMS. Methods: A systematic review of the medical literature was conducted to evaluate articles about primary CLMS. The literature was searched between 1959 and May 2019. On final evaluation, there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
7
1
Order By: Relevance
“…Primary cervical leiomyosarcomas constitute 21% of all cervical sarcomas. [8,10] Hysterectomy should be the first choice of treatment in these patients according to other studies. Multimodality management may suitable for cervical leiomyosarcoma.…”
Section: Discussionmentioning
confidence: 96%
“…Primary cervical leiomyosarcomas constitute 21% of all cervical sarcomas. [8,10] Hysterectomy should be the first choice of treatment in these patients according to other studies. Multimodality management may suitable for cervical leiomyosarcoma.…”
Section: Discussionmentioning
confidence: 96%
“…Of all diagnosed cervical sarcomas, leiomyosarcomas make up 21%8. In 2020, a systematic international review found 42 cases reported in the literature 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Performing a hysterectomy has been a significant predictor of disease-free survival. Still, the type of surgery (radical, modified radical, or extrafascial) does not indicate recurrence and has no impact on survival 7,14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A slight association between TIM-3 and OS was observed in the younger group ( P = 0.046). Some studies demonstrate an age effect going in different directions ( 73 75 ). For example, Zhang et al reported that age (the elder group) was associated with a poorer prognosis ( 73 ).…”
Section: Discussionmentioning
confidence: 99%